Entrepreneurial implications, prospects and dilemmas in rural festivals. (October 2018) - Hjalager, Anne-Mette; Kwiatkowski, Grzegorz
Abstract: Festivals play an important role in rural communities, and they are typically embedded in the local ecosystems of sports, culture, business and other types of associations, where they might deliver elements of coherence, commitment and meaning, as well as occasional economic benefits. This study aims to showcase the business entrepreneurship aspect of festivals in Danish rural areas, and it is based on primary data from 315 festivals. Special emphasis is placed on the nature, prevalence and importance of business activities at such festivals and on the opportunities for entrepreneurs to utilize festivals as a means of business development in relation to sales, marketing, product testing, and customer feedback. On the one hand, the results show that very few of the surveyed festivals are entirely commercial and that commercial objectives are, due to ideological and relational reasons, generally low-ranked by organizers. On the other hand, there is strong evidence that local businesses actually participate in rural festivals' ecosystems and that there are numerous mutual interactions among local businesses, festival organizers and residents that together create an excellent means for driving entrepreneurial activity. It is a delicate undertaking to strengthen partnerships with entrepreneurs without compromising community objectives. Several potential courses of action are proposed. Highlights: Business opportunities are ubiquitous in rural festivals in Denmark. For entrepreneurs, involvement in festivals may represent a way to gain market access and users' feedback. Due to more imperative community objectives, prospects for business remain unarticulated and possibly underexploited. There are ample opportunities to achieve entrepreneurial benefits from festivals without compromising community fundamentals.